Medication-related osteonecrosis of the jaw in a minipig model: Parameters for developing a macroscopic, radiological, and microscopic grading scheme. Issue 7 (July 2019) - Nowicki, B.; Nehrbass, D.; Arens, D.; Stadelmann, V.A.; Zeiter, S.; Otto, S.; Kircher, P.; Stoddart, M.J.
Abstract: Objectives: To devise a macroscopic, radiological, and histological scale for assessing pathological changes associated with medication-related osteonecrosis of the jaw in a minipig model. Materials and methods: Medication-related osteonecrosis of the jaw was induced in Göttingen minipigs by weekly intravenous administration of bisphosphonate (zoledronic acid) combined with a tooth extraction procedure. Controls either did not receive zoledronic acid or did not undergo tooth extraction. After 20 weeks, minipigs were euthanized and underwent computed tomography and micro-computed tomography scanning. The mandible underwent additional histological examination. Results: The most consistent macroscopic findings in animals that had developed bisphosphonate-related osteonecrosis of the jaw (BRONJ) were necrotic, denuded bone, and formation of fistula and pus. Under radiological examination, impaired extraction socket healing, decrease in attenuation of bone beneath the extraction site, and periosteal reaction were observed. Under histological examination, demineralization of the extracellular bone matrix, denuding of bone, and osteonecrosis were recorded. Conclusion: These parameters were used to develop a scoring system for grading BRONJ.